ANALISIS PENGGUNAAN COMPLETION FLUID GARAM BERAT NITRAT SEBAGAI HOLE CLEANING DAN PENGARUHNYA TERHADAP ZAT ADITIF - Indriani Agustina; Bayu Satiyawira; Mulia Ginting (President University, 2018)
Completion fluid is a fluid used in conducting operational completion, where the fluid used must be based on consideration of the formation characteristics for a particular well. Fluid selection is very important if the formation damage will be minimized. good complexion fluids can reduce solid content, absence of clay, solulable acid, dissolve in water and are used for operations such as perforation, cleaning wells and well control. The nitrate salts used are CaNO3 and NaNO3 salts. Agarfluida complexes can function properly, so the fluid must always be controlled for its physical properties, which consist of fluid specific gravity, fluid rhology, filter rate, swell meter and pH. The use of compound fluid is adjusted to the conditions of the formation that is being perforated such as formation rock formation conditions, and fluid content contained in the formation. This study will examine the use of fluid complexes from heavy salts of nitrates as hole cleaning and their effect on the additives used. It was concluded that the use of saline-complex fluid heavy with NaNO3 nitrate and its combination with the use of CaCO 3 had the effectiveness to carry out hole cleaning activities with the results of Plastic Viscosity 23 cp, 24 lbs / 100 ft Yield Point, 4.2 ml / 30 'Filtrate, pH 7, 41, and Swellmeter 6%.